2023
DOI: 10.1001/jamaoncol.2023.2780
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Analysis of Disparities in Access to Oncofertility Services

Abstract: ImportanceFertility preservation (FP), including oocyte and embryo cryopreservation prior to gonadotoxic therapy, is an urgent and essential component of comprehensive cancer care. Geographic proximity to a center offering FP is a critical component of ensuring equitable access for people with cancer desiring future fertility.ObjectiveTo characterize the distribution of centers offering FP services in the US, quantify the number of self-identified reproductive-age female individuals living outside of geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Prior studies have demonstrated geographic disparities in cancer care and access to ART. [23][24][25] A recent study by Peipert et al 26 used geospatial modeling to assess the distribution of oncofertility centers in the United States and found that 3.63 million reproductive-aged females lack access to oncofertility services and that states with fertility-preservation mandates have the highest rates of eligible female patients with geographic access. Our study supports and builds on this prior research by being the first to evaluate geospatial predictors of fertility-sparing treatment in addition to ART use and using health indices to predict the use of fertility-sparing treatment or ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated geographic disparities in cancer care and access to ART. [23][24][25] A recent study by Peipert et al 26 used geospatial modeling to assess the distribution of oncofertility centers in the United States and found that 3.63 million reproductive-aged females lack access to oncofertility services and that states with fertility-preservation mandates have the highest rates of eligible female patients with geographic access. Our study supports and builds on this prior research by being the first to evaluate geospatial predictors of fertility-sparing treatment in addition to ART use and using health indices to predict the use of fertility-sparing treatment or ART.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, legislation for state-mandated fertility preservation appears to be another means of decreasing geographic disparities. 26 Telemedicine has also demonstrated its potential to bridge geographical gaps and provide remote access to specialized care as well as reduce wait times to see specialists and may have benefits in both rural and urban settings. 29 Finally, the relative weights of the California Healthy Places Index domains provide additional insight into the types of interventions that may be most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, access and options to fertility preservation have evolved favorably in the U.S., including the emergence of state‐based fertility preservation insurance mandates 36 . However, a significant number of barriers to accessing oncofertility care remain, including lack of financial or geographic access, 37 lack of information and referral, and personal fear or uncertainty regarding fertility presentation. While we were unable to evaluate specific reasons for non‐utilization in our analysis, we believe that medical insurance coverage and cost of the procedures were factors that may have discouraged patients from pursuing these procedures, as demonstrated in prior studies 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, FP insurance mandates may have the potential to reduce disparities in geographic access to oncofertility care. Peipert et al demonstrated that patients in states with FP legislation had higher geographic access to oncofertility centers compared to states without FP legislation, as defined by the percentage of patients within a 2 h travel time to a center [38]. Although research is needed to elucidate the contributing factors underlying this association, the authors posit that FP insurance mandates could create an economic incentive for an increase in oncofertility centers.…”
Section: Utilization Based On Demographic Characteristicsmentioning
confidence: 99%